Prevalence and Risk Factors of Microalbuminuria in Nondiabetic Hypertensive Patients (Community Based Medical Journal, 2014)
The aim of this study to determine the prevalence of microalbuminuria as well as associated factors in non-diabetic hypertensive patients. Hospital-based cross sectional study. Main outcome of measure is microalbuminuria. A total of 100 nondiabetic hypertensive patients age 18 years without a history of pre-existing kidney disease attending the outpatient department of Community Based Medical College Bangladesh, Mymensingh over a period 6 months from June to December 2014 and who consented and met the criteria were enrolled in this study. A questionnaire including clinical and laboratory data was completed for all cases. The survey data were checked, coded and entered into a SPSS statistical package (Version 11.5). All variables were tested for normal distribution of the data. The data were then cleaned and analyzed using Chi-square (x2) Test, One-Way ANOVA statistics and Binary logistic regression model. Results were considered statistically significant for two-sided P values of